Optimization of cell unroofing and in vitro reconstitution of reticular adhesion - Quadir, Mohammed Mostafa Al (2024)
Reticular adhesions (RAs) are a novel type of cell-ECM adhesion, characterized by the presence of integrin αVβ5 and colocalized with flat clathrin lattices (FCLs) and lack many focal adhesion (FA) components. A distinctive feature of RAs is their persistence during the cytoskeletal changes that occur in cell division, unlike other cell adhesions that typically disassemble. The formation of RAs involves the clustering of integrin αVβ5 and the formation of FCLs, which have been found to be interdependent events. A deeper understanding of why this occurs and what physiological factors trigger RA formation is needed. The in vitro reconstitution of RAs is crucial for studying these questions in a controlled manner. This thesis aimed to optimize a method for isolating membrane sheets attached to a solid substrate. It compared two cell unroofing methods, which remove the top membrane and cytosol, leaving the bottom membrane on a solid surface: squashing-peeling and ultrasonication. It also attempted to reconstitute RAs on these membrane sheets and visualize them using TIRF microscopy. This experiment was successful in producing high-quality membrane sheets and in reconstituting RAs on these sheets. Among the two methods employed for generating the membrane sheets, ultrasonication was found to be more effective than the squashing-peeling method for isolating high-quality membrane sheets. The research also indicated that RA formation is temperature-sensitive, with 37°C being the optimal temperature. In vitro reconstitution of reticular adhesions presents a powerful approach to studying these novel structures.